1996
DOI: 10.1152/ajpheart.1996.270.2.h692
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extracellular buffer composition on cardioprotective efficacy of Na+/H+ exchanger inhibitors

Abstract: There is controversy over whether the cardioprotective effects of Na+/H+ exchanger inhibitors are exerted primarily during ischemia or during subsequent reperfusion, possibly because of interstudy differences in experimental conditions. We studied the impact of perfusate buffer composition on the relative degree of protection afforded by Na+/H+ exchanger inhibition during ischemia vs. reperfusion. Isolated rat hearts (n = 8/group) were perfused (37 degrees C, 75 mmHg) with bicarbonate- or N-2-hydroxyethylpiper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…Increased activity of the Na + /H + exchanger can cause Ca 2+ overload because the elevated intracellular Na + is subsequently exchanged for Ca 2+ via the Na + /Ca 2+ exchanger (Pierce and Czubryt, 1995). Inhibition of Na + /H + exchange has been shown to protect against ischemic injury, possibly by preventing this increase in Ca 2+ (Bond et al, 1993;Shimada et al, 1996). Conversely, inhibition of the vacuolar ATPase promotes apoptosis, in part by shifting the proton load towards the Na + /H + transporter, thereby increasing Ca 2+ uptake, and in part by reducing the myocyte capacity to control intracellular pH (Gottlieb et al, 1996;Karwatowska-Prokopczuk et al, 1998;Long et al, 1998).…”
Section: Regulation Of Ph During Ischemiamentioning
confidence: 99%
“…Increased activity of the Na + /H + exchanger can cause Ca 2+ overload because the elevated intracellular Na + is subsequently exchanged for Ca 2+ via the Na + /Ca 2+ exchanger (Pierce and Czubryt, 1995). Inhibition of Na + /H + exchange has been shown to protect against ischemic injury, possibly by preventing this increase in Ca 2+ (Bond et al, 1993;Shimada et al, 1996). Conversely, inhibition of the vacuolar ATPase promotes apoptosis, in part by shifting the proton load towards the Na + /H + transporter, thereby increasing Ca 2+ uptake, and in part by reducing the myocyte capacity to control intracellular pH (Gottlieb et al, 1996;Karwatowska-Prokopczuk et al, 1998;Long et al, 1998).…”
Section: Regulation Of Ph During Ischemiamentioning
confidence: 99%
“…This finding is consistent with previous reports that provide evidence that Na ϩ /H ϩ exchange inhibitors are more effective when given before ischemia rather than at the time of reperfusion. 27,28 …”
Section: ؉ Overload and Ph I On Reperfusionmentioning
confidence: 99%
“…On the basis of previous reports that the acylguanidine moiety is a pharmacophore of NHE-1 inhibitors (Shimada et al, 1996), we have focused on finding novel NHE-1 inhibitory guanidine analogues. In such attempts, we found that a new guanidine derivative, [5-(2-methoxy-5-chloro-5-phenyl)furan-2-ylcarbonyl]guanidine (KR-32570) showed a greater potency against NHE-1 activity compared to cariporide, and markedly improved cardiac contractile function in isolated rat heart ischemic model (Lee et al, 2005a,b).…”
Section: Introductionmentioning
confidence: 99%